Research on Big Data Mining and Solutions Based on Computer Cloud Computing. Issue 2 (October 2020) - Zhang, Jianshi
Abstract: The application of computer cloud computing has profoundly changed the way the world works and brought people an everlasting experience. In order to adapt to the development direction of information technology, we need to deeply understand the current situation of big data application and study the innovative application of data mining technology.